(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Computer graphics are the main technology in digital photography, cinema, video games, digital art, mobile phone and computer displays, as well as in many specialized applications. A variety of specialized hardware and software has been developed, with most devices equipped with graphics hardware.